The circumstellar environment of the star V923 Aquilae - Arias, María Laura (2004)
V923 Aquilae is a Be shell star that displays emission in Hα, cyclic V/R variations and variations in the intensity of the near infrared continuum. The star presents radial velocity variations arising from a superposition of a long-term cycle and an orbital motion with a period of 214.756 days (Koubský et al. 1989). To investigate the physical properties and the geometry of the circumstellar envelope of this star, we have analysed its spectra in the UV and visual range. We have selected Fe II lines to derive temperatures and location of the line-forming regions. Our results indicate that the dimensions of the circumstellar envelope vary with time and this variation correlates with the orbital period of 214.75 days. On the other hand, we determined a period of 6.8 years for V/R cyclic variations in Hα. This period is in accordance with the long-term cycle in the radial velocity and U band photometric observations. We suggest that the V/R variability in the Hα line is linked to the behavior of the subsonic wind structure.